2017
DOI: 10.1371/journal.pone.0177664
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of basal and lipopolysaccharide-induced microRNA expression in equine peripheral blood mononuclear cells using Next-Generation Sequencing

Abstract: The innate immune response to lipopolysaccharide contributes substantially to the morbidity and mortality of gram-negative sepsis. Horses and humans share an exquisite sensitivity to lipopolysaccharide and thus the horse may provide valuable comparative insights into this aspect of the inflammatory response. MicroRNAs, small non-coding RNA molecules acting as post-transcriptional regulators of gene expression, have key roles in toll-like receptor signaling regulation but have not been studied in this context i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…From a confirmative viewpoint, these findings are similar to those reported for human SEs (34), suggesting that these miRNAs can be involved in similar modulatory processes in both species. Furthermore, the let-7 family of miRNAs as well as mir-21 are highly abundant in equine serum and plasma and also expressed in diverse tissue types (59,(75)(76)(77)(78)(79)(80). Validation of the miRNA sequencing data by RT-qPCR confirmed specific downregulation of eca-mir-128 in long-term persistently infected stallions, an intronic miRNA encoded by two distinct genes, eca-mir-128-1 and eca-mir-128-2, located on (81).…”
Section: Discussionmentioning
confidence: 82%
“…From a confirmative viewpoint, these findings are similar to those reported for human SEs (34), suggesting that these miRNAs can be involved in similar modulatory processes in both species. Furthermore, the let-7 family of miRNAs as well as mir-21 are highly abundant in equine serum and plasma and also expressed in diverse tissue types (59,(75)(76)(77)(78)(79)(80). Validation of the miRNA sequencing data by RT-qPCR confirmed specific downregulation of eca-mir-128 in long-term persistently infected stallions, an intronic miRNA encoded by two distinct genes, eca-mir-128-1 and eca-mir-128-2, located on (81).…”
Section: Discussionmentioning
confidence: 82%
“…For example, in response to LPS equine bone marrow-derived macrophages do not produce nitric oxide unlike rodents which do (Young et al, 2018). Several studies have highlighted that the horse immune response is more similar to that of human than mouse (Karagianni et al, 2017;Parkinson et al, 2017). Additionally, sequence analysis of human, rodent and horse genes involved in immunity have demonstrated greater synteny between horse and human than rodent and human (Hudgens et al, 2011;Tompkins et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in other mammalian‐derived cells, TLR2 ligands induce a mild inflammatory response in equine PBMC; this is in comparison to the much greater response to TLR4 agonists 9,89 . Recent transcriptomic studies have reported that LPS induces differential microRNA expression in equine PBMC in a manner comparable to humans, thus facilitating interspecies comparative study of the role of microRNAs in the inflammatory cascade during endotoxaemia and sepsis 90 . Equine monocytes are also responsive to TLR3 stimulation with double‐stranded RNA (polyinosinic polycytidylic acid [Poly IC]), 91 which is dependent upon the TRIF adaptor.…”
Section: The Mononuclear Phagocyte System Of the Horsementioning
confidence: 88%